Characterization of soil chemical properties for stable and unstable slope as hazard monitoring rating system for shallow slope failure - Othman, Rashidi; Hasni, Mohd Shah Irani; shaharuddin, Ruhul izzati; Mohd. Radzi, Noor Shakilah (2015)
Shallow slope failure is the problem that seem like have no ending in the highway construction field in Malaysia. Most of the oxisols in Malaysia is highly weathered and thus it is essential to study the soil properties between stable and unstable slope in terms of chemical characteristics that will lead to the factors of shallow slope failure. The aim of the study is to characterize chemical properties of stable and unstable slope of oxisols soils from 5 sites along highways in Malaysia. Chemically, clay contents, micronutrient contents, soil texture, soil pH value, cation exchange capacity (CEC), organic carbon contents, nitrogen contents, phosphorus content, and heavy metal contents are the important elements in soil that could make the soil structure strong or weak. All of them have various relationships to each other, as indicator and binding agents that affects the strong soil structure. Shallow slope failure have strong relationship between CEC and hydrogen content in the soil because both play an important role in binding the negative and positive charges in soil that lead to the stability of the soil structure. In conclusion, indicators that can be used to predict shallow slope failure are low content of Aluminum (Al), Ferum ( Fe), Plumbum (Pb),Zinc (Zn), Chromium ( Cr), low content of organic carbon and CEC .